Avaliação da substituição total de areia natural por RCD em revestimentos de argamassa - Girardi, Aline Crispim Canedo (2016)
Although the use of CDW in the aggregate production is studied in Brazil for more than two decades, there are still gaps regarding their use in mortars. In this sense, the present study aims to evaluate mortar for rendering masonry produced with full replacement of natural sand by recycled aggregate, seeking to correlate the various properties and characteristics of aggregates and mortars with the performance of rendering with regard to the adhesive strength and absorption/water permeability. For the development of the research three types of aggregates were used (natural sand, mixed recycled ceramic and cement and cementitious recycled) in two particle sizes, passers-by screens 3 mm and 1.18 mm, which were widely characterized. With the data obtained in the characterization of aggregates, different traces were formulated for mortars, keeping fixed the content of total fine plasticizers. The mortars were evaluated on their consistency, bulk density, dimensional instability (shrinkage), water absorption, compressive and flexural strength. The renderings were applied on ceramic blocks, which were selected for initial water absorption rate ranges, avoiding the variability of results due to changes in the suction of the substrate. Two types of preparation of the base were performed, lime solution and roughcast, the latter was used only for the rendering that showed the best performance among those produced with recycled aggregates. As the main results, it was found that using a sieve with an opening of 1.18 mm is effective for reducing the content of fine aggregate, however, mortars and renderings produced with these aggregates showed unsatisfactory performance, falling short of results in materials with through 3 mm sieve. Mortars and rendering produced with recycled aggregate cement did not show compatible performance with the others, at the expense of the initial assumptions, which provided that this aggregate would exceed the aggregate mixed. It was also noticed that the recycled aggregates mixed ceramic and cementitious material, passers the sieve 3 mm, despite the high content of fine and high water absorption, resemble very to the natural aggregate with the same granulometry, when comparing the characteristics of mortars they have produced, mainly for resistance to compression. When assessing the rendering produced by these two aggregates, both are equivalent in the question of adhesive strength and showed no cracking. In general, it can be concluded that it is feasible the production of efficient rendering with complete replacement of natural sand for mixed recycled aggregates since the RCD origin and characteristics are known, Provided that limited the packing factor of grain , which directly influence the properties of mortars and renderings.